Molecular data confirm the species status of Neoechinorhynchus personatus and N. yamagutii (Acanthocephala, Neoechinorhynchidae) from the Atlantic and Pacific grey mullets (Teleostei, Mugilidae) - Sarabeev, Volodimir; Tkach, Ie.; Sueiro, R. A.; Leiro, J. (Zoodiversity, 2020)
Neoechinorhynchus is known to be the most diverse acanthocephalan taxon with worldwide distribution; its species are characterized by uniformity of anatomical organization. The taxonomic status of Neoechinorhynchus agilis s. l. from grey mullets was recently reviewed that resulted in description of two new species, Neoechinorhynchus (Hebesoma) personatus and Neoechinorhynchus (Hebesoma) yamagutii. In the current study,18S rRNA partial gene sequences were obtained to molecularly characterize N. (N.) agilis, N. (H.) personatus and N. (H.) yamagutii from grey mullets, Chelonlabrosus and Mugil cephalus, in the North-East Atlantic, the Japan, Azov and Mediterranean Seas. The universal (F-566 and R-1200) and specific eukaryotic set primers were used to amplify specimens from each species of Neoechinorhynchus. It has been found that three species can be clearly recognized using universal primers, which allow to obtain sequences of 590 to 664 bp in length. The genetic divergences estimated between three species sequenced here were relatively high, at ranged between 2.08 and 6.57 %. Phylogenetic analysis demonstrates that the studied species of Neoechinorhynchus from grey mullet fish share common ancestor, despite their different geographic location, and are closely related. The terminal position of N. (N.) agilis and N. (H.) personatus on the evolution tree and the low genetic divergence found between them suggests the recent emergence of this group and that the colonization of the North-East Atlantic and the Mediterranean regions could represent a single event. Our phylogenetic analysis, which included several species of the subgenera Neoechinorhynchus and Hebesoma, showed that the latter is a polyphyletic taxon.